Potensi Buah Jamblang (Syzygium cumini (L.) sebagai Agen Anti-Kanker yang Efektif pada Manusia - Andita Wahyuning Pramesti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Cancer is a malignant disease caused by the abnormal growth of cells in body tissues, making it one of the leading causes of death worldwide. The high prevalence of cancer has driven the search for new, effective, and safe anti-cancer agents, one of which involves utilizing phytochemical compounds from plants such as Java plum (Syzygium cumini), which has attracted attention as a potential anti-cancer agent due to its therapeutic potential and low toxicity. This literature review examines recent studies on the anti-cancer activity of Java plum across various cancer types through in vitro studies. The results show that Java plum exhibits several key mechanisms in inhibiting cancer cell growth, including induction of apoptosis, cell cycle arrest, inhibition of cell proliferation, ROS production, targeting of cancer stem cells, anti-inflammatory effects, modulation of epigenetic changes, and antioxidant protection.